A 2X2 MIMO Patch Antenna for Multi-Band Applications - Islam, Md Rafiqul; Abdulrab, Waheeb Salim; Rafiq, Sarah; Yasmin, M S; Habaebi, Mohamed Hadi (Institute of Advanced Engineering and Science (iaes) Indonesia, 2017)
In this paper, a Multiple Input Multiple Output (2x2MIMO) patch antenna for multiband applications has been proposed. It has been designed using groups of rings nearby the stepped cut at four corners of the patch and a separation in mid slot. This modification is proposed in order to increase the resonant frequencies and reduce the mutual coupling. The proposed 2x2 MIMO patch antenna is simulated using Computer Simulation Technology (CST), fabricated and tested. With such small geometrical dimensions, the proposed antenna is suitable for LTE (1.8 GHz), WiFi (2.4 GHz), and WiMax (3.5 GHz, 5.2 GHz and 5.5 GHz) applications. Keywords: Multiple Input Multiple Output (MIMO), Envelope correlation coefficient (ECC), Computer Simulation Technology (CST), Multi-Band Applications